OVERIVEW OF COLORING PLAY THERAPHY ON THE ANXIETY LEVEL OF PRESCHOOL-AGED CHILDREN A DUE TO HOSPITALIZATION AT THE PADAMARA HEALTH CENTER, PURBALINGGA REGENCY - Rysca Ramadhani Arista Dewi; Dwi Astuti; Priyatin Sulistyowati (PT. Jurnal Center Indonesia Publisher, 2025)
Background: Preschool-Aged children, aged 3–6 years, where the preschool period becomes a very fun time and get various new things. The weakness experienced by preschool children is that their immune system is weaker than adults, which makes them more susceptible to infections, as well as the risk of falls and injuries, so they require medical treatment in the hospital. Childern who undergoing treatment at the Puskesmas can cause anxiety for them because they must leave their familiar, safe, loving, and enjoyable home environment. Hospitalization is a planned medical procedure that requires care and treatment but can trigger anxiety in children, both mentally and physically. Anxiety will cause children to become uncooperative and difficult to cooperate with health workers. During this process, children may face traumatic experiences that cause stress. One of the efforts to reduce the level of anxiety is by implementing play therapy, one of which is the coloring play therapy technique. Objective: This research describes the application of coloring play therapy on anxiety levels in preschool-aged children at Padamara Health Center. Methods: This research used a case study research design method. Results: This research indicate that before the intervention score was 25 (moderate anxiety) and after the intervention score was 9 (no anxiety). Conclusion: Coloring play therapy can reduce anxiety levels in preschool-aged children undergoing treatment at Padamara Health Center.